WAGE DISPARITY A CHALLENGE FOR WOMEN WORKERS WORKING - GUNJA KUMARI (International Journal of Multidisciplinary Research and Studies, 2020)
On the other hand, in both developed and developing nations, workers who are illiterate or have only completed primary education are more likely to be employed in informal settings than individuals who have completed secondary and higher levels of education. This is due to the fact that workers who are illiterate or have only completed primary education are less likely to have access to formal employment opportunities. The following table, which is based on the official secondary data source known as the Periodic Labour Force Survey (PLFS), includes some estimates of the many different types of informal labor, as well as the numerous features of informality when viewed through the lens of gender (2017–18).